Immunogenetic predisposing factors for mesial temporal lobe epilepsy with hippocampal sclerosis. (3rd April 2018) - Leal, Bárbara; Chaves, João; Carvalho, Cláudia; Bettencourt, Andreia; Brito, Cláudia; Boleixa, Daniela; Freitas, Joel; Brás, Sandra; Lopes, João; Ramalheira, João; Costa, Paulo P.; da Silva, Berta Martins; et al.
ABSTRACT: Purpose: Neuroinflammation appears as an important epileptogenic mechanism. Experimental and clinical studies have demonstrated an upregulation of pro-inflammatory cytokines such as IL-1β and TNF-α, in mesial temporal lobe epilepsy with hippocampal sclerosis (MTLE-HS). Expression of these cytokines can be modulated by polymorphisms such as rs16944 and rs1800629, respectively, both of which have been associated with febrile seizures (FS) and MTLE-HS development. The human leukocyte antigen (HLA) system has also been implicated in diverse epileptic entities, suggesting a variable role of this system in epilepsy. Our aim was to analyse the association between immunogenetic factors and MTLE-HS development. For that rs16944 (-511 T>C, IL-1β), rs1800629 (-308 G>A, TNF-α) polymorphisms and HLA-DRB1 locus were genotyped in a Portuguese Population. Methods: We studied 196 MTLE-HS patients (108 females, 88 males, 44.7 ± 12.0 years, age of onset = 13.6 ± 10.3 years, 104 with FS antecedents) and 282 healthy controls in a case–control study. Results: The frequency of rs16944 TT genotype was higher in MTLE-HS patients compared to controls (14.9% in MTLE-HS vs. 7.7% in controls, p = 0.021, OR [95% CI] = 2.20 [1.13–4.30]). This association was independent of FS antecedents. No association was observed between rs1800629 genotypes or HLA-DRB1 alleles and MTLE-HS susceptibility. Also, no correlation was observed between the studied polymorphisms and disease age of onset. Conclusion: The rs16944 TT genotype is associated with MTLE-HS development what may be explained by the higher IL-1β levels produced by this genotype. High IL-1β levels may have neurotoxic effects or imbalance neurotransmission leading to seizures.